JURIDICAL ANALYSIS OF SHARE OWNERSHIP OF UNDERAGE CHILD IN THE BANKRUPTCY OF THEIR PARENTS AS A GUARDIAN IN PT. ARGA DUMILAH - Rina Alamanda Nasution; Sunarmi Sunarmi; T. Keizerina Devi Azwar; Detania Sukarja (NOMOI Law Review, 2022)
Juridically, Parents represent Minors to carry out all legal actions both inside and outside the court. One of them is that parents are obliged and responsible for the management of their children's assets, both for the ownership of these assets and for all the results of the goods that they are allowed to enjoy . Parents are not allowed to transfer their rights or pledge their children's property except for the interests of the child. Ownership of shares in the name of Minors is a form of investment as capital in a limited liability company and ownership rights to shares are obtained by inheritance. This research uses a normative juridical legal research method with a descriptive qualitative research model, and prioritizes the main data in the form of primary, secondary and tertiary legal materials. This study refers to legal theories, legal norms, legal principles and legal theories contained in legislation and court decisions.